Strategic Plan for the Five-Year Non-Tuition Fee Revenue Program at Politeknik Elektronika Negeri Surabaya (PENS - Rizki Widya Ridhani; Mas Roro Lilik Ekowanti; Sri Umiyati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the development strategy of the Business Unit programs at Politeknik Elektronika Negeri Surabaya (PENS) in supporting non-tuition fee revenue, as well as to examine the internal and external factors influencing these strategies. This research employs a qualitative methodology based on John M. Bryson’s strategic planning theory, with data analyzed through a SWOT (Strengths, Weaknesses, Opportunities, and Threats) framework. Data were gathered through in-depth interviews with Business Unit leadership and supplemented by secondary data from supporting documents. The analysis results, as illustrated in the Cartesian diagram, indicate that the Business Unit is positioned in Quadrant I, suggesting that development should be pursued through a Strength–Opportunity (SO) strategy. Based on these findings, a five-year strategic plan was developed to serve as a recommendation for the future strategic direction of Politeknik Elektronika Negeri Surabaya